Acute Gravitational Stress Selectively Impairs Dynamic Cerebrovascular Reactivity in the Anterior Circulation Independent of Changes to the Central Respiratory Chemoreflex - Watanabe, Hironori; Saito, Shotaro; Washio, Takuro; Bailey, Damian Miles; Ogoh, Shigehiko (Frontiers in Physiology, 2022)
Cerebrovascular reactivity (CVR) to changes in the partial pressure of arterial carbon dioxide (PaCO2) is an important mechanism that maintains CO2 or pH homeostasis in the brain. To what extent this is influenced by gravitational stress and corresponding implications for the regulation of cerebral blood flow (CBF) remain unclear. The present study examined the onset responses of pulmonary ventilation (VE) and anterior middle (MCA) and posterior (PCA) cerebral artery mean blood velocity (Vmean) responses to acute hypercapnia (5 % CO2) to infer dynamic changes in the central respiratory chemoreflex and cerebrovascular reactivity (CVR), in supine and 50° head-up tilt (HUT) positions. Each onset response was evaluated using a single-exponential regression model consisting of the response time latency [CO2-response delay (t0)] and time constant (τ). Onset response of VE and PCA Vmean to changes in CO2 were unchanged during 50° HUT compared with supine (τ: VE, P = 0.707; PCA Vmean, P = 0.071 vs. supine) but the MCA Vmean onset response was faster during supine than during 50° HUT (τ: P = 0.003 vs. supine). These data indicate that gravitational stress selectively impaired dynamic CVR in the anterior cerebral circulation whereas the posterior circulation was preserved, independent of any changes to the central respiratory chemoreflex. Collectively, our findings highlight the regional heterogeneity underlying CBF autochemoregulation that may have translational implications for the microgravity (and hypercapnia) associated with deep-space flight notwithstanding terrestrial orthostatic diseases that have been linked to accelerated cognitive decline and neurodegeneration.